Analysis of Curly Red Chili Farming - Pinem, Egi Tri Saputra; Anak Agung Ayu Wulandira Sawitri Djelantik (Faculty of Agriculture Udayana University, 2025)
BACKGROUND AND OBJECTIVES Buahan Village, located in the Kintamani District of Bangli Regency, is recognized as one of the most fertile areas that supports agricultural activities, particularly the cultivation of curly red chili. However, farmers in Buahan Village face several challenges in growing curly red chili, including pest and disease attacks that cause decay in the leaves and stems of the plants. Moreover, they are experiencing rising production costs each year, especially in plant maintenance, such as fertilizers, pesticides, and other chemical inputs. These challenges have led to a decline in production and an increase in farming expenses. The decrease in yield has resulted in a shortage of chili supply, leading to price fluctuations. METHODS This study uses a descriptive quantitative method. Data were collected through questionnaires and structured interviews with 33 farmers, who were selected using accidental sampling. Primary data was obtained directly from respondents, while secondary data came from documents and written references. Data analysis included: 1) Calculation of revenue, 2) Calculation of income, and 3) Measurement of the feasibility of the R/C ratio of curly red chili farming. FINDINGS The average revenue of curly red chili farmers reached Rp 38,409,712 with a cultivated land area of 31 ares in one planting season. The net income earned by these farmers was Rp 15,869,267, which was calculated by subtracting the total costs of Rp 22,540,445 from the total income of Rp 38,409,712 during the same season. The profitability of curly red chili farming is 1.7, which is greater than 1. This means that for every Rp 1 spent, farmers earn Rp 1.70, indicating that curly red chili farming is viable and financially worthwhile. CONCLUSION The average revenue of curly red chili farmers reaches IDR 38,409,712 with a cultivated land area of 31 ares in one planting season. The total costs incurred by red chili pepper farmers during one growing season amount to Rp 22,540,445. The income earned by red chili pepper farmers reaches Rp 15,699,267 with a cultivated land area of 31 ares per growing season. The profitability of red chili farming reaches a value of 1.7, where > 1. This means that every expenditure of Rp 1 will yield an income of Rp 1.7, making red chili farming viable and worth pursuing.